Nilai-nilai Kesabaran dan Kasih Sayang dalam Kitab Waṣāyā Al-Ābā’ Lil Abnā’ Karya Syaikh Muhammad Syākir Al-IskandarῙ - Ahmad Mulki Lubis; Faisal Musa; Puli Taslim Nasution (Prodi Pendidikan Keagamaan Islam, 2024)
This study aims to examine the values of patience (ṣabr) and compassion (raḥmah) contained in Waṣāyā al-Ābā’ lil Abnā’, a moral treatise written by Shaykh Muhammad Shākir al-Iskandarī, and to identify the supporting virtues that reinforce these two main values. The research is motivated by the urgency of cultivating noble character amid the growing moral and social challenges of the modern era. This study employs a qualitative method using a library research approach, in which the primary source the manuscript of the book is analyzed through content analysis techniques. The findings reveal that the value of patience in this work encompasses steadfastness, perseverance, and self-control in facing life’s trials. Meanwhile, the value of compassion is reflected through the encouragement to do good to family members, respect parents, help others, and show kindness to the weak. Supporting virtues that strengthen these moral principles include consistency (istiqāmah), optimism, determination, responsibility, and discipline. Shaykh Muhammad Shākir harmonizes firmness of principle with gentleness of expression, making the moral messages practical, applicable, and relevant to daily life. The study concludes that Waṣāyā al-Ābā’ lil Abnā’ provides a significant contribution to the formation of Islamic character education based on patience and compassion. Therefore, these values are recommended to be integrated into character education programs within families, educational institutions, and communities.